Solid-liquid extraction of gallic acid from Kacip Fatimah (Labisia pumila Benth. & Hook. f.) leaves - Awang, Mohd Azrie (2014)
Labisia Pumila or known as Kacip Fatimah is one of medicinal plants which are rich of bioresource for traditional systems of medicine, food supplements and pharmaceutical intermedtiates. According to scientific researches, the leaf of this plant is proven to posses many beneficial bioactivities and its leaf extract has great potential to be used in developing naturally occurring commercial products in market demand. However, very little research has been carried out with regards to the processing of bioactive extract of L. pumila leaves.This research studied a solidliquid extraction (SLE) process which involved processing of the bioactive extract from L. pumila leaves. Experiments were carried out to determine the effects of various operating parameters on the qualitative and quantitative aspects of L. pumila leaves. Gallic acid (GA) was selected as the quality indicators of the product because this compound played a major role in the bioactivities including anti-inflammatory, antioxidant activity, anti-microbial, anti-cancer and prevention of osteoporosis. Water was found to be most suitable solvent for extracting gallic acid from L. pumila leaves compared to other organic solvents. It gave the highest extraction yield as well as quality extract of GA. It also showed the highest antioxidant and antiinflammatory. The optimum extraction condition of L. pumila leaves were determined as 80°C and the ratio of water to solid is 30:1 (ml:g) based on analysis using Response Surface Methodology (RSM) technique. An equilibrium driven solid liquid extraction (EDSLE) model was developed and successfully applied in describing the process.